Papel das calcificações vasculares mamárias na predição do risco cardiovascular - Mendonça, Roberto Moreno (2018)
Cardiovascular diseases (CVD) are the leading cause of death worldwide, constituting one-third of all deaths in women. Carriers of coronary artery disease (CAD) presented a silent evolution, so it is important to identify those who present the highest risk of developing events. Clinical scores using traditional risk factors to predict the risk of the individual having a cardiac event, however, these algorithms have limited capacity. Several studies have demonstrated the ability of Coronary Calcium Score (CCS) to predict mortality and cardiovascular events independently in addition to other risk factors. Parallel to this, mammography (MMG) is the only method available for population screening of breast cancer, but also could identify the atherosclerosis process, referred to as breast vascular calcification (BVC). We verified if there is an association between the BVC and CCS, thus predicting cardiovascular risk (CVR) in women whose MMG revealed BVC. An observational, analytical study included women submitted to MMG and CCS at the Universidade Federal do Rio Grande do Norte/Brazil and Instituto de Radiologia de Natal between June/2015-September/2016. A systematic random sampling selected 51 patients, reassessed for the presence of BVC and CCS. Aggravating factor of CVR was considered to be a CCS greater than 100 and/or percentile above 75%. The mean age of the patients was 56.47 years; 68.6% did not present BVC. In these patients, 83% presented CCS compatible with low CVR. In those with BVC, there was an equal distribution between the CCS considered as low and high CVR, with prevalence ratio = 2.91 and prevalence odds ratio = 4.83 (P = 0,015). BVC specificity and accuracy was 82.9% and 72.5%, respectively.